Low Soluble Programmed Cell Death Protein 1 Levels After Allogeneic Stem Cell Transplantation Predict Moderate or Severe Chronic GvHD and Inferior Overall Survival - Kordelas, Lambros; Buttkereit, Ulrike; Heinemann, Falko M.; Horn, Peter A.; Giebel, Bernd; Beelen, Dietrich W.; Reinhardt, H. Christian; Rebmann, Vera (Frontiers in Immunology, 2021)
Programmed cell death protein-1 (PD-1) is an inhibitory co-receptor required for regulating immune responsiveness and maintaining immune homeostasis. As PD-1 can be released as bioactive soluble molecule, we investigated the clinical significance of soluble PD-1 (sPD-1) after allogeneic hematopoietic stem cell transplantation (HSCT) regarding graft-versus-host disease (GvHD), relapse, and overall survival (OS) in a mono-centric cohort of 82 patients. Compared to pre-HSCT and to healthy controls, post-HSCT sPD-1 plasma levels were significantly increased during an observation time of three months. Univariate analysis revealed that low sPD-1 plasma levels at month one, two or three post HSCT were associated with acute GvHD grade III-IV, the onset of moderate/severe chronic GvHD (cGvHD) and inferior OS, DFS, and TRM, respectively. No relationship was detected to relapse rates. sPD-1 plasma levels were significantly increased in ATG-treated patients compared to ATG-untreated patients. Multivariate analysis revealed that a low sPD-1 plasma levels status at one or two month(s) after HSCT is an independent indicator for inferior OS, DFS, or TRM. A low sPD-1 plasma levels status at month three post HSCT is predictive for the onset of moderate/severe cGvHD. Thus, our study pinpoints the soluble inhibitory co-receptor PD-1 as a promising candidate molecule for the prediction of clinical HSCT outcome.